Characterization of a New Thermoalkalophilic Xylanase-Producing Bacterial Strain Isolated from Cimanggu Hot Spring,West Java, Indonesia (Indonesian Society for microbiology, 2011)
Alkalophilic bacteria and their enzymes are important for industrial applications. Therefore, finding out new strains of alkalophilic bacteria from Indonesian microbial diversity is still required. In this study, a thermoalkalophilic bacterium was isolated from sediment of local hot spring, Cimanggu,West Java. The temperature of the spot was 60 °C and the pH was 8. The bacterium could live at pH 11 and temperature 55 °C, and produced xylanase that have optimal activity at alkaline pH 9 and high temperature 70 °C. Based on the analyses of 16S rRNA sequence similarity and biochemical characteristics, this strain was clustered into the same group of Bacillus halodurans species with 99% identity to Bacillus halodurans C-125. The isolate also showed other enzyme activities such as amylase, protease, and gelatinase, promising its potential use as an industrial enzymes producer.